Moringa oleifera seeds as natural coagulant for water treatment - Ali , Eman N; Muyibi, Suleyman Aremu; Salleh, Hamzah Mohd.; Salleh, Mohd Ramlan M.; Alam, Md. Zahangir (2009)
Developing countries and third world countries are facing potable water supply problems because of inadequate financial resources. The cost of water treatment is increasing and the quality of river water is not stable due to suspended and colloidal particle load caused by land development and high storm runoff during the rainy seasons especially in a country like Malaysia. During the rainy seasons the turbidity level increases and the need for water treatment chemicals increase as well, which leads to high cost of treatment which the water treatment cannot sustain. As a result, the drinking water that reaches the consumer is not properly treated. Therefore, it is of great importance to find a natural alternative for water coagulant to treat the turbidity. It has been found that Moringa oleifera is the best natural coagulant discovered yet, that can replace aluminium sulphate (Alum) which is used widely all around the world. The study is focusing in Moringa oleifera seeds to find the active constituents which are responsible about the coagulation mechanism and improving the coagulation property. This will help in producing this alternative locally as Moringa oleifera is grown in Malaysia and other tropical countries and can be of great benefit for water treatment.